Land Subsidence Assessment in the Darab Plain, Fars Province, Iran: Integrating Sentinel-1 InSAR and Groundwater Level Data - Luqman Othman; Jabar Majidi; Alan Amini (Advances in Civil Engineering and Environmental Science, 2025)
Withdrawing groundwater leads to a drop in the water table and soil consolidation, which can eventually cause land subsidence. This phenomenon can have significant negative impacts on infrastructure, agriculture, and the environment, as well as lead to reduced agricultural productivity.  This study investigates the relationship between land subsidence and groundwater level decline in the Darab Plain, Fars Province, using Sentinel-1 satellite imagery and groundwater data from May 2017 to May 2019. To examine groundwater level variations in the Darab Plain, data from 31 piezometric wells were utilized. These wells were strategically distributed throughout the study area to ensure comprehensive spatial coverage. The Inverse Distance Weighting (IDW) interpolation method was employed to visualize the spatial distribution of groundwater level decline. Results show a maximum subsidence of 4.5 cm and a groundwater decline of 18 meters, with a strong correlation (72%) between the two variables. The findings highlight the need for sustainable groundwater management to mitigate subsidence risks.